Psycholinguistic approach to the study of aphasia - V, Balasubramanian (Journal of All India Institute of Speech and Hearing, 1971)
Speech is the best show man puts on’ said Benjamin Lee Whorf. This ’best show’ is one among the characteristic forms of human behaviour. In this paper, an attempt is made to give a critical account of the contributions made by Psycholinguists in understanding the impaired show put up by a few persons in the clinical condition known as aphasia.